Artificial size selection experiment reveals telomere length dynamics and fitness consequences in a wild passerine. Issue 23 (27th January 2022) - Pepke, Michael Le; Kvalnes, Thomas; Rønning, Bernt; Jensen, Henrik; Boner, Winnie; Sæther, Bernt‐Erik; Monaghan, Pat; Ringsby, Thor Harald
Abstract: Telomere dynamics could underlie life‐history trade‐offs among growth, size and longevity, but our ability to quantify such processes in natural, unmanipulated populations is limited. We investigated how 4 years of artificial selection for either larger or smaller tarsus length, a proxy for body size, affected early‐life telomere length (TL) and several components of fitness in two insular populations of wild house sparrows over a study period of 11 years. The artificial selection was expected to shift the populations away from their optimal body size and increase the phenotypic variance in body size. Artificial selection for larger individuals caused TL to decrease, but there was little evidence that TL increased when selecting for smaller individuals. There was a negative correlation between nestling TL and tarsus length under both selection regimes. Males had longer telomeres than females and there was a negative effect of harsh weather on TL. We then investigated whether changes in TL might underpin fitness effects due to the deviation from the optimal body size. Mortality analyses indicated disruptive selection on TL because both short and long early‐life telomeres tended to be associated with the lowest mortality rates. In addition, there was a tendency for a negative association between TL and annual reproductive success, but only in the population where body size was increased experimentally. Our results suggest that natural selection for optimal body size in the wild may be associated with changes in TL during growth, which is known to be linked to longevity in some bird species. Sammenfatning: Telomerdynamik kan ligge bag afvejninger mellem livshistorietræk såsom vækst, kropsstørrelse og livslængde, men vores evne til at kvantificere sådanne processer i naturlige, umanipulerede bestande er begrænset. Vi har undersøgt hvorledes 4 års kunstig selektion for enten større eller mindre tarsuslængde, et estimat for kropsstørrelse, påvirkede telomerlængden (TL) i det tidlige liv, samt overlevelses‐ og formeringsevner, i to øbestande af vilde gråspurve over en periode på 11 år. Vores forventning var, at den kunstige selektion ville skubbe bestandene væk fra deres optimale kropsstørrelse og øge den fænotypiske varians i kropsstørrelse. Kunstig selektion for større individer forårsagde en reduktion i TL, men der var begrænset evidens for en øgning i TL når vi selekterede for mindre individer. Der var en negativ korrelation mellem fugleungernes TL og tarsuslængde under begge selektionsregimer. Hanner havde længere telomerer end hunner og der var en negativ effekt af ugunstige vejrforhold på TL. Dernæst undersøgte vi om ændringer i TL kunne underbygge effekter på overlevelses‐ og formeringsevner som følge af afvigelsen fra den optimale kropsstørrelse. Analyser af dødeligheden indikerede disruptiv selektion på TL fordi både korte og lange telomerer i det tidlige liv viste tendens til at være associeret med de laveste dødelighedsrater. Derudover var der en tendens til en negativ sammenhæng mellem TL og årlig reproduktiv succes, men kun i bestanden hvor kropsstørrelse var øget eksperimentelt. Vores resultater antyder, at naturlig selektion for optimal kropsstørrelse i vildtlevende dyr kan være associeret med ændringer i TL (i løbet af vækstperioden), som er kendt for at være forbundet med levetid hos nogle fuglearter.